Sarcodia suiae Water Extract Promotes the Expression of Proinflammatory and Th1-Type Cytokines and Delay the Onset of Mortality in Cobia (Rachycentron canadum) During Photobacterium damselae subsp. damselae Infection - Lee, Po-Tsang; Nan, Fan-Hua; Chiu, Po-Yu; Tseng, Chung-Chih; Lee, Meng-Chou (Frontiers in Immunology, 2022)
Cobia (Rachycentron canadum) is a marine fish of high economic value that grows at a fast rate. However, intensive fish farming has led to disease outbreaks in cobia cultures, which is highly costly to the industry. The impact of infectious diseases on cobia production has led to the inappropriate and increased use of chemicals and antibiotics, which negatively affects the environment and human health and promotes the spread of drug-resistant pathogens. Hence, prophylactic measurements, such as the use of immunomodulators, are required to improve the health of cultured animals against pathogens. In this study, we examined the effects of Sarcodia suiae water extract (SSWE) in cobia in vitro and in vivo. We found that treatment with SSWE could significantly increase the expression of cytokines (e.g., IL-1β, IL-6, IL-10, IL-12, and TNF-α) and chemokines (e.g., IL-8) in primary cultured head kidney leukocytes. Intraperitoneal injection of SSWE (20 μg/g body weight) promoted higher expression of IL-6, IL-8, IL-10, IL-12, chemokines (e.g., CC1), and antibodies (e.g., IgT) in head kidney and spleen tissues of the fish compared with other dose levels. Additionally, we describe for the second time (only after India) of isolation of Photobacterium damselae subsp. damselae (Phdd) from a deadly epizootic in cage-farmed cobia. An intraperitoneal inoculation of SSWE before Phdd challenge showed that SSWE treatment could delay the onset of mortality of cobia. Finally, fish that received SSWE intraperitoneally before infection with Phdd exhibited elevated expression of Th1-type cytokines, including IL-8, IL-12, TNF-α, and IFN-γ. At the same time, the expression of Th2-related factors (such as IL-10 in the head kidney, and IgM and IgT in the spleen) were lower for the fish that received SSWE instead of PBS before the Phdd challenge. The results indicate that SSWE treatment facilitates the induction of Th1-type cytokines in cobia to fight against Phdd infection and has the potential to be used as an immunostimulant and vaccine adjuvant for fish.